Survey of Theileria parasites of sheep in eastern Turkey using polymerase chain reaction - Aktas, M; Altay, K; Dumanli, N (Elsevier Science Bv, 2005)
This Study provides the first molecular data on infection Theileria of sheep in Turkey. A total of 218 blood samples were collected from sheep in five distinct geographical locations of eastern Turkey. Theileria piroplasm DNAs, extracted from sheep blood, were subjected to the polymerase chain reaction (PCR) procedures, using specific primers for Theileria spp. and Theileria lestoquardi. Blood smears were examined for Theileria piroplasms by microscopic observation. In PCR analysis, the expected amplicons were obtained from 90 (41.2%) blood samples with a molecular size of 1098 bp for Theileria spp. whereas none were amplified by Theileria lestoquardi-specific primers. Piroplasms of Tewileria spp. were detected in 34 (15.5%) of the samples. (c) 2005 Published by Elsevier B.V.
Keywords: Theileria; sheep; PCR